Improving the Management Capability of the Giyanti Tourism Village in to Raise the Tourism Village Category - Endah Trihayuningtyas; Renalmon Hutahean; Tatang Sopian; Mohammad Liga Suryadana; Haryadi Darmawan (Politeknik Negeri Bandung, 2023)
This study aims to improve the management capability of the Giyanti tourism village in Wonosobo Regency, Central Java. The village has a cultural uniqueness (USP) that is not shared by other villages in Wonosobo Regency in the form of the lengger dance. At present, with the designation of an emerging tourism village, the Giyanti tourism village is still classified as an embryo tourism village. This study used a qualitative descriptive method using data collection techniques through observation, in-depth interviews and literature studies. In improving the qualifications of tourism villages, it can be carried out through four (4) stages, namely 1) tourism village planning, 2) tourism village organization, 3) tourism village development implementation, 4) tourism village evaluation and monitoring. Diversification of Giyanti village products based on culture is needed as well as strengthening the ability of human resources in managing tourist attractions and collaboration with surrounding tourism villages can be strategic steps in increasing the capabilities and the classification of tourism villages.